Pendapatan neto dan biaya pemasaran terhadap laba bersih pada perusahaan hiburan di Indonesia - Suhartati, Suhartati; Ekasari, Juendiny Chrisna; Ray, Ayuvera Rifani (Nur Science Institute, 2025)
The entertainment industry in Indonesia is experiencing rapid growth, but tight competition requires companies to manage their finances efficiently. Net profit is a key indicator of a company's financial performance, influenced by various factors, including net income and marketing costs. Net income reflects the company's ability to generate a profit, while marketing costs play a role in driving sales, but can also be a burden. This study aims to examine the impact of net revenue and marketing expenses on net profit in the Indonesian entertainment industry. The sample comprises 10 entertainment companies, utilizing secondary data derived from their annual financial reports over the past three years: 2020, 2021, and 2022. The analytical method employed in this research is multiple linear regression, which is used to examine both the simultaneous and partial effects between the independent variables and the dependent variable. The results indicate that net revenue has a positive and significant impact on net profit, while marketing expenses show varied effects depending on each company’s internal conditions. This study is expected to serve as a reference for strategic decision-making in financial and marketing planning, particularly in efforts to improve profitability in the Indonesian entertainment industry.